2014
DOI: 10.1007/s10517-014-2336-0
|View full text |Cite
|
Sign up to set email alerts
|

Adaptogenic Effects of Dihydroquercetin–Chitosan Composition during Modeling of Acute Hypoxia

Abstract: The course of preventive oral treatment with a dihydroquercetin-chitosan composition produced a strong antihypoxic effect under conditions of experimental hypobaric hypoxia (arbitrary altitude 12,000 m). The lactate/pyruvate ratio in composition-receiving rats was much lower than in hypoxic animals (by 83%), but higher than in intact specimens (by 29%). The composition of chitosan and dihydroquercetin also possessed a strong antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Dihydroquercetin (DHQ) ((2R,3R)-2-(3,4-dihydroxyphenyl)-3,5,7-trihydroxy-2,3-dihydrochromen-4-one) is a flavonoid commonly found in onions ( 16 ) , milk, thistle ( 17 ) and French maritime bark ( 18 ) . This polyphenol is classified as an antioxidant ( 19 ) and meets two of the three criteria for effective radical scavenging ability – the presence of the o -dihydroxy structure in the B ring conferring stability and the 5- and 7-OH groups with 4-oxo function in the A and C rings that are responsible for a maximum radical scavenging potential. In addition to its antioxidative effect, DHQ has been shown to have beneficial properties in cancer, CVD and liver diseases ( 20 ) .…”
mentioning
confidence: 99%
“…Dihydroquercetin (DHQ) ((2R,3R)-2-(3,4-dihydroxyphenyl)-3,5,7-trihydroxy-2,3-dihydrochromen-4-one) is a flavonoid commonly found in onions ( 16 ) , milk, thistle ( 17 ) and French maritime bark ( 18 ) . This polyphenol is classified as an antioxidant ( 19 ) and meets two of the three criteria for effective radical scavenging ability – the presence of the o -dihydroxy structure in the B ring conferring stability and the 5- and 7-OH groups with 4-oxo function in the A and C rings that are responsible for a maximum radical scavenging potential. In addition to its antioxidative effect, DHQ has been shown to have beneficial properties in cancer, CVD and liver diseases ( 20 ) .…”
mentioning
confidence: 99%
“…Interestingly, the adaptogenic effect of taxifolin (dihydroquercetin) has been the subject of two studies, in which the authors confirmed that the formulation of taxifolin with chitosan as a vehicle produced a strong antihypoxic effect under conditions of experimental hypobaric hypoxia, with the lactate/pyruvate ratio much lower in the group of rats that received the taxifolin than in hypoxic animals ( Baranov et al, 2015;Murach et al, 2014). However, it is believed that the sum effect of a crude extract is most probably a synergy of different pharmacologically active compounds present in the extract, which might be responsible for the adaptogenic effect of HEHt (Wagner, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have found that TAX bound to glyoxalic acid condensation could become a new compound consisting of two TAX unit dimers, having more effective anti-oxidant effects than TAX [ 152 ]. In addition, TAX-chitosan compositions were found to present more apparent anti-hypoxia actions in the process of preventive oral therapy under experimental hypoxia conditions than TAX alone [ 153 ]. On the other hand, in order to improve the bioavailability of TAX, γ-cyclodextrin (γ-CD) was employed as an inclusion complex.…”
Section: Bioavailability Of Taxmentioning
confidence: 99%